2013
DOI: 10.1109/rbme.2012.2236311
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Robotic Platforms for Minimally Invasive Surgery

Abstract: Recent technological advances in surgery have resulted in the development of a range of new techniques that have reduced patient trauma, shortened hospitalization, and improved diagnostic accuracy and therapeutic outcome. Despite the many appreciated benefits of minimally invasive surgery (MIS) compared to traditional approaches, there are still significant drawbacks associated with conventional MIS including poor instrument control and ergonomics caused by rigid instrumentation and its associated fulcrum effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
191
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(239 citation statements)
references
References 101 publications
0
191
0
10
Order By: Relevance
“…Such an approach may be adequate for performing very simple procedures, however a more sophisticated endoscopic platform is needed for more complex thoracic surgery. Equipment used for NOTES can be categorized into two groups: flexible equipment and miniaturized devices (7,8). These devices, some of which are merely prototypes for NOTES, have their own advantages and disadvantages, which are summarized in Table 1.…”
Section: Natural Orifice Transluminal Endoscopic Surgery (Notes) Platmentioning
confidence: 99%
“…Such an approach may be adequate for performing very simple procedures, however a more sophisticated endoscopic platform is needed for more complex thoracic surgery. Equipment used for NOTES can be categorized into two groups: flexible equipment and miniaturized devices (7,8). These devices, some of which are merely prototypes for NOTES, have their own advantages and disadvantages, which are summarized in Table 1.…”
Section: Natural Orifice Transluminal Endoscopic Surgery (Notes) Platmentioning
confidence: 99%
“…A number of devices targeting flexible access applications for Natural Orifice Transluminal Endoscopic Surgery (NOTES) have surgical instruments integrated at the front of flexible endoscopes, such as the ANUBISCOPE ® (iCUBE STRAS) robot developed at IRCAD-Strasbourg, that is based on the Karl Storz ® Anubis ® system, the R-scope and Endo-Samurai by Olympus. A review of such flexible access NOTES systems can be found in [10]. Although promising, these systems still lack of adequate stability, triangulation and force exertion capabilities to carry out complex tissue manipulation, as required during TEMS.…”
Section: Introductionmentioning
confidence: 99%
“…Continuum robots are emerging surgical platforms that can navigate through the human anatomy to reach deep-seated pathological sites [2], [3]. A representative continuum robot is the concentric tube robot [4], [5].…”
Section: Introductionmentioning
confidence: 99%